1995
DOI: 10.1111/j.1476-5381.1995.tb15141.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endotoxin on sympathetic responses in the rat isolated perfused mesenteric bed; involvement of nitric oxide and cyclo‐oxygenase products

Abstract: 1 The effects of endotoxin on the vasoconstrictor responses to sympathetic nerve stimulation (SNS) were investigated in the rat isolated perfused mesenteric bed. 2 Rats received either saline (0.1 ml h-') or endotoxin (2.5 mg kg-' h-') intravenously for 4 h; the mesenteric beds were then isolated, perfused with Krebs and prepared for SNS (50 V, 3 ms,. 3 SNS caused a frequency-dependent vasoconstrictor response which was abolished by either tetrodotoxin (10-7 M), prazosin (2.4 x 10-7M) or guanethidine (2.4 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Lack of alterations in the mesenteric vascular contractility to NE after LPS administration, at a time when iNOS activity was indeed increased, is in accordance with previous studies with adrenergic agonists (Mitchell et al, 1993;Fatehi-Hassanabad et al, 1995;Eerdmans et al, 1996). Nevertheless, hyporeactivity to NE in perfused mesenteric beds after LPS administration was described previously (MitoloChieppa et al, 1996) and lower responses to methoxamine were observed when this agonist was administered as an infusion instead of as a bolus (Farmer et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Lack of alterations in the mesenteric vascular contractility to NE after LPS administration, at a time when iNOS activity was indeed increased, is in accordance with previous studies with adrenergic agonists (Mitchell et al, 1993;Fatehi-Hassanabad et al, 1995;Eerdmans et al, 1996). Nevertheless, hyporeactivity to NE in perfused mesenteric beds after LPS administration was described previously (MitoloChieppa et al, 1996) and lower responses to methoxamine were observed when this agonist was administered as an infusion instead of as a bolus (Farmer et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…It has been documented, by using different experimental models, that LPS can induce an increase in the spontaneous release of ACh at the neuromuscular junction (41). In rabbit airways, LPS-induced AHR involved activation of vagal C fibers and the release of neuropeptides (42); moreover, LPS augmented contractile responses and noradrenaline overflow evoked by EFS stimulation in the small mesenteric artery and in the tail (43).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this is due to modulation of cardiac autonomic transmission. First, NO can attenuate the cardiac responses to sympathetic stimulation both by inhibiting neuronal noradrenaline release [37] at the prejunctional level [38] and by inhibiting its effects on cardiac β-adrenoceptors [39]. This would be one explanation of why NO, released for example during preconditioning [40] and exercise or following the administration of NO donors [41], is able to reduce the severity of ischaemia-induced ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%